2022
DOI: 10.1155/2022/8094385
|View full text |Cite|
|
Sign up to set email alerts
|

miR-206 Targets MALAT1 to Suppress Cell Progression of Ectopic Endometrial Stromal Cells in Endometriosis

Abstract: Background. miR-206 was reported to be a tumor suppressor in bladder cancer. In this study, we explore the expression and function of miR-206 in endometriosis (EM). Methods. 40 EM patients undergoing total hysterectomy were selected as the experimental group. RT-qPCR assay was adopted to detect the expression of MALAT1 and miR-206 in EM. Cell proliferation was detected by EdU incorporation and colony formation assay. Cell migration and invasion viability of ESCs were examined by transwell assay and wound heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%